Relationship Of Pregnant Mother's Anxiety Levels During The Covid-19 Pandemic On ANC Visit At Puskesmas Sukatani Bekasi - Wiwit Astuti; Sri Dinengsih; Shinta Novelia (Universitas Islam Lamongan, 2021)
The spread of the Covid-19 pandemic in Indonesia has made vulnerable groups more susceptible to contracting this virus. One of these vulnerable groups is pregnant women. More and more pregnant women in Indonesia are positive for Covid-19. Pregnant women who are infected with the Covid-19 virus are more likely to give birth to babies early in premature conditions. During the Covid-19 pandemic, many pregnant women were afraid to have their pregnancy checked. Anxiety when they want to do a pregnancy check is often felt by pregnant women during a pandemic corona virus. Analytical research using the